PROJECT-BASED LEARNING IN ENGLISH LANGUAGE TEACHING: A PATHWAY TO PRACTICAL SKILLS - Jumaniyazova Lobar Sirojiddin qizi (TADQIQOTLAR, 2025)
ABSTRACT Project-Based Learning (PBL) has emerged as a student-centered method that encourages critical thinking, collaboration, and language production in meaningful contexts. In English Language Teaching (ELT), PBL serves not only as a teaching strategy but also as a bridge between academic learning and real-world application. This article investigates the use of PBL in ELT and how it improves learners’ speaking, writing, and problem-solving skills. Based on current literature and classroom case studies, the findings suggest that PBL promotes learner autonomy, motivation, and practical language use. Despite challenges such as time limitations and assessment complexities, PBL remains an effective methodology for fostering communicative competence. This paper argues for wider adoption of PBL in ELT, supported by teacher training and flexible curricula.